2023
DOI: 10.1186/s13054-023-04507-5
|View full text |Cite
|
Sign up to set email alerts
|

Time to treatment and mortality for clinical sepsis subtypes

Abstract: Background Sepsis is common, deadly, and heterogenous. Prior analyses of patients with sepsis and septic shock in New York State showed a risk-adjusted association between more rapid antibiotic administration and bundled care completion, but not an intravenous fluid bolus, with reduced in-hospital mortality. However, it is unknown if clinically identifiable sepsis subtypes modify these associations. Methods Secondary analysis of patients with sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…In addition, the probability for unobserved confounding to substantially contribute to our findings was tested, implying that considerable unmeasured confounding, above and beyond all measured confounders, would be necessary to explain away the observed effect estimate. Although acknowledging the limitations of E-values in estimating residual confounding (20,(49)(50)(51)(52), we believe that there is a low probability that unobserved confounding significantly biased our results. Data from a limited geographical region were analyzed and the findings might therefore not be generalizable to other healthcare settings.…”
Section: Limitationsmentioning
confidence: 77%
“…In addition, the probability for unobserved confounding to substantially contribute to our findings was tested, implying that considerable unmeasured confounding, above and beyond all measured confounders, would be necessary to explain away the observed effect estimate. Although acknowledging the limitations of E-values in estimating residual confounding (20,(49)(50)(51)(52), we believe that there is a low probability that unobserved confounding significantly biased our results. Data from a limited geographical region were analyzed and the findings might therefore not be generalizable to other healthcare settings.…”
Section: Limitationsmentioning
confidence: 77%
“…Sin embargo, este cumplimien- A partir de las nuevas definiciones de sepsis 1 y la revisión de las guías que se publicaron poco después, nuestro SUH adoptó el algoritmo de actuación conocido como paquete de medidas en las primeras 3 horas 4 . Aunque se ha discutido sobre el beneficio de aplicar estas medidas en la primera hora, su aplicación en los pacientes mayores de 65 años es controvertida 13,14 . A pesar de que el manejo actual supone una mejoría con respecto a estudios previos realizados en este mismo centro 15 , se observa que no se cumple en todos los casos, especialmente en los pacientes muy añosos, lo cual se discute a continuación.…”
Section: Discussionunclassified
“…In these cases, timely and appropriate antimicrobial treatment is crucial. Studies have shown that delays in starting such treatment, or the use of inappropriate antimicrobial regimens, are linked to increased mortality rates (2)(3)(4)(5)(6)(7)(8). Despite the well-recognized importance of early and appropriate antibiotic therapy in managing sepsis, adherence to this principle has been disappointingly low.…”
Section: Introductionmentioning
confidence: 99%